HUMAN COLLABORATION AT WORK challenge and potential in creative relationships. - Berg, David N., 1949- (ROUTLEDGE, 2025)
Human Collaboration at Work delves into the dynamics of collaboration between two individuals, examining both the challenges and potential in creative relationships and offering a useful resource for all those working with others. The two-person relationship is one of the key building blocks in our understanding of relationships in organizations yetis largely understudied in the literature. This book brings the dyadic relationship to the fore and offers support for those engaging in collaborative relationships in the workplace and beyond. The author reframes challenges as opportunities for partners to leverage their differences and overcome potential conflicts. Through this lens, he provides a nuanced understanding of the interpersonal and contextual factors that influence collaboration. Supported by compelling real-life examples, including the author's own long-term working relationship with a colleague, this book is an essential guide for those in leadership roles, managers, consultants, and academics alike - anyone seeking to enhance their collaborative relationships in professional settings.
Keywords: Interpersonal relations.; Business communication.; elektronické knihy; electronic books